The 100 000 Genomes Project: bringing whole genome sequencing to the NHS. (24th April 2018) - Turnbull, Clare; Scott, Richard H; Thomas, Ellen; Jones, Louise; Murugaesu, Nirupa; Pretty, Freya Boardman; Halai, Dina; Baple, Emma; Craig, Clare; Hamblin, Angela; Henderson, Shirley; Patch, Christine; et al.
Abstract : In partnership with NHS England, Genomics England's ambitious plans to embed genomic medicine into routine patient care are well underway. Clare Turnbull and colleagues discuss its progress